2006
DOI: 10.1002/ajmg.a.31295
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone therapy and scoliosis in patients with Prader–Willi syndrome

Abstract: Growth hormone (GH) therapy for short stature in patients with Prader-Willi syndrome (PWS) has started worldwide, and various favorable effects have been reported. However, the possibility of progression of scoliosis arises as a new problem of the GH therapy. In this study, we analyzed whether 72 patients who have been followed up in our hospital have such a problem. They included 46 males and 26 females (41 patients with the GH therapy and 31 without it) aged from one to 49 years. Consequently, 33 (45.8%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 19 publications
5
38
1
Order By: Relevance
“…Similar to previously published data [30,31,32], 31% of children receiving GH treatment had scoliosis in our study. The prevalence increased with age but was already high in young children (14% in patients were under 5 years).…”
Section: Discussionsupporting
confidence: 82%
“…Similar to previously published data [30,31,32], 31% of children receiving GH treatment had scoliosis in our study. The prevalence increased with age but was already high in young children (14% in patients were under 5 years).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, Nagai et al showed that height velocity is not increased in patients with Prader-Willi syndrome who have scoliosis and receive GH therapy versus their counterparts those who do not [3]. Thus, a greater growth response to GH therapy is not a risk factor for scoliosis.…”
Section: Growth Response To Gh Therapymentioning
confidence: 99%
“…Second, the possibility of deterioration in scoliosis was suggested, although we have particularly reported that there was no connection between the frequencies of scoliosis in GH treatment and non-treatment groups [14,15]. Based on the backgrounds of these studies, GH treatment has recently been recommended at an early age, and it is assumed that its long-term use is not a problem.…”
Section: Discussionmentioning
confidence: 96%